2012
DOI: 10.1021/ma301902d
|View full text |Cite
|
Sign up to set email alerts
|

Functional Thin Films Resulting from Parylene–Vinyl Copolymerization

Abstract: Quantum and kinetic studies of novel materials based on parylene polymers and variously substituted vinyl molecules are presented and discussed. It is demonstrated that the thin films which are the products of the copolymerization reactions can be prepared (i) within the parylene CVD process on active vinyl substrates or (ii) employing the same process but involving an additional source of vinyl molecules transported to the reaction chamber. Both methods lead to differently functionalized microstructures, prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…One explanation for this was the sample's compositional inhomogeneity due to reactor geometry, as already explained (Figure 3). The presence of longer PPXblocks in the copolymers is also supported by quantum calculations on reactivity ratios of p-xylylene units with vinylic/acrylic comonomers in CVD copolymerizations made by Bobrowski et al 19 They showed that p-xylylene is far more reactive compared to the comonomer, and therefore is the dominant species in the copolymer chains over a wide range of monomer feed ratios. The occasionally random distribution of comonomer units along the chain, as described by Bobrowski et al, is also supported by the presence of multiple carbonyl resonances in 13 C-NMR, as discussed above.…”
Section: Copolymer Propertiesmentioning
confidence: 67%
See 2 more Smart Citations
“…One explanation for this was the sample's compositional inhomogeneity due to reactor geometry, as already explained (Figure 3). The presence of longer PPXblocks in the copolymers is also supported by quantum calculations on reactivity ratios of p-xylylene units with vinylic/acrylic comonomers in CVD copolymerizations made by Bobrowski et al 19 They showed that p-xylylene is far more reactive compared to the comonomer, and therefore is the dominant species in the copolymer chains over a wide range of monomer feed ratios. The occasionally random distribution of comonomer units along the chain, as described by Bobrowski et al, is also supported by the presence of multiple carbonyl resonances in 13 C-NMR, as discussed above.…”
Section: Copolymer Propertiesmentioning
confidence: 67%
“…17,18 These studies have evoked further theoretical interest in the copolymerization mechanism and reactivity of p-xylylene moieties with conventional double bond containing monomers. 19,20 In this work, we copolymerized alkyl substituted [2.2] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is caused by the fact that the vinyl and etin polymerizations are characterized generally by higher reaction barriers; many such processes require catalizers. Copolymerization of vinyl and parylene leads almost always (for various substituents present in vinyl moieties) to only insubstantial presence of vinyl units in the parylene main chains [12]. Hence the reveal that one possible unfolding for achievement of higher molar ratio for vinyl molecules in parylene-based copolymers might be the decrease of relative reactivity of parylene N, C and D’s monomers for instance by substitution of a larger amount of hydrogen atoms both in aromatic ring as well as in aliphatic segments.…”
Section: Resultsmentioning
confidence: 99%
“…For optimized products and for transition states found the characterization of extremes was performed by calculating various geometry, energy and charge properties. The choice of chloro-substituted p-xylylenes for polymerization reactions was dictated by the absence of the collective polymerization of parylene and styrene [15] in spite of the fact that p-xylylenes and some alkenes indeed react with each other as it was proven by FT-IR, FT-Raman and XPS spectra [12, 13, 42]. On the other hand, the substitution of terminal hydrogen atoms (in aliphatic positions) by chlorine atoms in p-xylylene makes the copolymerization feasible and 7,7,8,8-tetrachloro-p-xylylene as well as 2,5,7,7,8,8-hexachloro-p-xylylene copolymerize well with styrene, vinyl acetate, acrylonitryle and methyl methacrylate as it has also been proven experimentally [31].…”
Section: Discussionmentioning
confidence: 99%